an J Health Educ Health Promot 2019
DOI: 10.30699/ijhehp.7.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Frankl’s Logotherapy on Health (Decreasing Addiction Potential and Increasing Psychological Well-being) of Students with Depression

Abstract: Background and Objective: Depression is one of the most common psychological problems that can increase addiction potential and decrease psychological well-being. There are different methods to improve the psychological status of people and logotherapy is one of them. As a result, present research aims to determine effectiveness of Frankl's logotherapy on addiction potential and psychological well-being of girl students with depression. Methods: This was a semi-experimental study with a pre-test and post-test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…One study of students with problematic drinking behaviors reported that both meaning of life and depressive symptoms improved after six sessions of logotherapy [ 44 ]. In another study, students’ addiction potential decreased while their psychological well-being increased [ 45 ]. Therefore, since the addiction potential and psychological well-being of college students were altered through logotherapy, it may have long term positive effects on their drug- or alcohol-related behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…One study of students with problematic drinking behaviors reported that both meaning of life and depressive symptoms improved after six sessions of logotherapy [ 44 ]. In another study, students’ addiction potential decreased while their psychological well-being increased [ 45 ]. Therefore, since the addiction potential and psychological well-being of college students were altered through logotherapy, it may have long term positive effects on their drug- or alcohol-related behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some exercises that could be placed within the framework of logotherapy were also included [ 42 ], since their objective was to learn to overcome the existential void that arises from the lack of meaning in what we do and in the life we lead, and to take responsibility in this way for our own life. Logotherapy has demonstrated to be effective in the treatment of different problems including addictions, depression, anger, anxiety, and for fostering psychological well-being [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, some exercises that could be placed within the framework of logotherapy were also included [43], since their objective was to learn to overcome the existential void that arises from the lack of meaning in what we do and in the life we lead, and to take responsibility in this way for our own life. Logotherapy has demonstrated to be effective in the treatment of different problems, including addictions, depression, anger, anxiety, and for fostering psychological well-being [44,45] The effectiveness of Flow meditation has been tested in various treatment studies with acceptable size effects (Amutio, et al, , 2018Franco et al, 2016). [34,35,36,46], The program includes existential, ethical and spiritual aspects and values, and thus conforms to Van Gordons´ criteria for Second Generation Mindfulness-Based Interventions (SG-MBIs) [47].…”
Section: Methodsmentioning
confidence: 99%